Preliminary Studies on Acute Oral Toxicity Effects of Dietary Supplement Derived from Scaphium scaphiugerum (G.DON) Fruit. - Reungpatthanaphong, Sareeya; Phatvej W; Sematong T; Phoonsiri C; Arunpairojana V (Thai Journal of Toxicology, 2020)
Scaphium scaphigerum fruit (Malva nut; in Thai “Phungthalai” or “Samrong”) has been used as food and a traditional medicine in many Asian countries. It has been used in folklore medicine to treat many diseases such as fever, diarrhea, kidney and large intestine disorders. In this research, the water extract of Malva nut is an active ingredient of dietary supplement which is proposed to be used as a health promoting agent and immunostimulant in human body. Therefore, it is interesting to evaluate the oral toxic effect of dietary supplement derived from Scaphium scaphigerum fruit (SCD). The objective of this study was to establish and investigate oral toxic effects of the SCD in animal testing. The acute oral toxicity study and chromosome analysis of the SCD were conducted by following the Test Guidelines No. 420 and No. 475 of the OECD guidelines for testing of chemical, respectively. The results of this study showed that an oral administration of the SCD at a dose of 5,000 mg/kg body weight to Wistar rats did not cause toxicity or death and did not cause chromosomal aberrations in the rat bone marrow cells.